Thermal decomposition characterization and kinetic parameters estimation for date palm wastes and their blends using TGA. (15th February 2023) - Alsulami, Radi A.; El-Sayed, Saad A.; Eltaher, Mohamed A.; Mohammad, Akram; Almitani, Khalid H.; Mostafa, Mohamed E.
Highlights: Detailed physicochemical characterizations of date palm wastes and their blend were measured. KAS and OFW models were used to estimate pyrolysis kinetic parameters. Increasing heating rates shifted TG profiles to higher temperature ranges. Date palm waste pyrolysis was profitable at high heating rates. This comprehensive study could be useful for future combustion studies of date palm wastes. Abstract: TGA has been used to evaluate the thermal degradation profiles and kinetic parameters for the pyrolysis of date leaves, date seeds, and leaf stems and their blend at various heating rates ( β ) in N2 . Using Kissinger–Akahira–Sunose (KAS), and Ozawa-Flynn-Wall (OFW), kinetic parameters like activation energy ( E ) and frequency factor ( A ) were estimated. The diffusion, reaction order, and power law models were used to estimate the frequency factors based on the ( E ) values obtained from the OFW and KAS approaches. Thermal degradation profiles showed two major loss processes: volatilization of cellulose, hemicelluloses, and lignin; and slow oxidation of the residual char. The findings demonstrated that as β increased, the TG profiles shifted to higher temperature ranges. The date palm's decomposition was not favourably reflected by the high (ΔGav ) values obtained. The high (ΔSav ) values obtained using OFW compared to KAS confirm these materials' high reactivity. The average activation energies ( Eav ) for the different parts of the date palm wastes ranged between 86 and 117 kJ/mole as predicted by the KAS method, while they were between 92 and 120 kJ/mole using the OFW method. The calculated frequency factor ( A ) values, evaluated by the KAS and the OFW methods, ranged between 0.0 and ∼ 0.8 × 10 19 min - 1 . The difference in ( E av ) values between the KAS and OFW techniques is no greater than 8 kJ/mole. For the diffusion models of DSW, DL, and Blend, the best frequency distribution profiles are essentially normal, and the blend exhibits high frequency ( A ) values in a relatively constrained range of ( α ). That denotes quick and efficient pyrolysis. The pyrolysis index (CPI) significantly increased as β increased, indicating that pyrolysis was profitable at high heating rates. The volatile release index (Ddev ) increases significantly with increasing ( β ) value, showing that volatiles was easier to release at a high heating rate.